Memaknai Wuwung Mbaru Gendang dan Relevansinya bagi Realitas Keagamaan Era Kontemporer - Cimi, Severinus Savio; Wijanarko, Robertus; Adon, Mathias Jebaru; Riyanto, FX Armada (Balai Penelitian dan Pengembangan Agama Semarang, 2024)
This research is motivated by the reality of the decadence of religious life in this day and age. On the one being many people begin to lose awareness of the importance of religion in building human life. However, on the other side, religious people are increasingly showing a discrepancy between the essential purpose of religious existence and their social behavior. Based on this reality, this article aims to elaborate some philosophical reflections on religious life today based on the symbols in the wuwung mbaru gendang of the Manggarai people. As an important part of the traditional house of the Manggarai people, the wuwung mbaru gendang has a meaning that is relevant to the religious issues of today. Its meaning will be elaborated based on Paul Ricoeur's theory of Symbol Interpretation. The direction of this article is the discovery of meanings in the wuwung mbaru gendang to be used as introspective material for researchers in reading the religious context of their era. The method used is literature study and direct observation of the object studied. The findings are first, the three symbols on the wuwung mbaru gendang reveal human identity as a noble creature. That nobleness is what spurs humans to make the highest respect for humans regardless of their religious background. Secondly, the quality of one's relationship with others can always be attributed to how one builds his or her spiritual-religious aspect. Vertical relations with the Ultimate Reality always get their continuity in good horizontal relations with others.